Novel potential therapeutic targets of alopecia areata - Xu, Wen; Wan, Sheng; Xie, Bo; Song, Xiuzu (Frontiers in Immunology, 2023)
Alopecia areata (AA) is an autoimmune disorder that causes non-scarring hair loss. An essential factor in AA is the immunity collapse of the hair follicle, where interferon-gamma (IFN-γ) and CD8+ T cells accumulate around the hair follicle. However, the exact functional mechanism has not been fully elucidated. Thus, AA treatment suffers from poor maintenance of efficacy and easy relapse after drug discontinuation. Recent studies demonstrated that immune-related cells and molecules could influence AA. Immune cells exchange autocrine and paracrine signals among themselves. Various cytokines, chemokines, and growth factor-mediated signals regulate this crosstalk. Additionally, adipose-derived stem cells (ADSCs), gut microbiota, hair follicle melanocytes, non-coding RNAs, and specific regulatory factors play crucial roles in intercellular communication, providing potential new targets for AA therapy. This review focuses on the latest research on the causes of AA and potential therapeutic targets.